(untitled) (Journal of Population and Development, 2021)
Remittance is the backbone of Nepalese’s economy in the present time. This study analyses the wellbeing of the remittance receptive household in the Melamchi Municipality of the Sindhupalchok District. Primary data were used as the main sources of information and secondary data were also used as supplementary sources. Primary data were collected by the direct personal interview through the semi-structural questionnaire survey of the sample area people who were selected by judgmental sampling method. Descriptive statistics has been used as the tools of data analysis of wellbeing of the remittance receptive households. Main destination of the employees of the sample area people is Malasia and Golf-country and they had used unorganized sectors as the sources of financing. Bank and money transfer had been used for the sources of money transfer in the sample area migrants. In the sample area people used, remittance has emerged as one of the major sources of income earning and they used that amount for their wellbeing. They increase their living standard through health facility, education facility and purchase of durable and comfortable goods. They invest for land and house purchase but not invest for the production as well as business. It has played a vital role in changing the lifestyle of the sample area people.